2007
DOI: 10.1016/j.jns.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Vascular dementia in leukoaraiosis may be a consequence of capillary loss not only in the lesions, but in normal-appearing white matter and cortex as well

Abstract: We investigated capillary density in 12 subjects with leukoaraiosis (LA), in 9 age-matched normal subjects, in 7 cases of Alzheimer's disease (AD), and 4 after whole-brain irradiation for brain tumors. In the LA study (which as been published), autopsy brains were evaluated by MRI. The presence of LA was indicated by confluent or patchy areas of hyperintensity in the deep white matter. We employed a stereology method using computerized image processing and analysis to determine microvascular density. Afferent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
129
3
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(149 citation statements)
references
References 16 publications
8
129
3
4
Order By: Relevance
“…Capillary loss has been reported in the white matter in vascular dementia in leukoaraiosis [53], decreased vascular density has been found in Alzheimer's disease, and cerebrovascular dysfunction precedes and accompanies cognitive dysfunction and neurodegeneration [54]. These data suggest that capillary abnormalities in the prefrontal cortex in schizophrenia detected in the present study might contribute to cognitive impairments in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 66%
“…Capillary loss has been reported in the white matter in vascular dementia in leukoaraiosis [53], decreased vascular density has been found in Alzheimer's disease, and cerebrovascular dysfunction precedes and accompanies cognitive dysfunction and neurodegeneration [54]. These data suggest that capillary abnormalities in the prefrontal cortex in schizophrenia detected in the present study might contribute to cognitive impairments in schizophrenia patients.…”
Section: Discussionsupporting
confidence: 66%
“…Currently, it is possible to find 2 main hypotheses in the literature regarding LA etiology: ischemic and nonischemic. According to the first theory, LA is caused by insufficient blood supply to the cerebral white matter due to the vascular pathology, 11,[37][38][39] and recent articles 40,41 demonstrated that vessel attenuation in the deep white matter was significantly lower in patients with LA compared with healthy subjects (P ϭ .018). According to the nonischemic hypothesis, LA may be due to the dilation of the perivascular spaces that surround normal arterioles or to atrophic changes that include gliosis or the loss of the myelinated axons seen in the normal-aging brain.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] Histologic studies have also demonstrated that vessel narrowing and/or outright vessel loss occurs with advancing age. 11,29,30 Although these histologic studies generally address vessels of a diameter smaller than can be seen by MRA, both a reduction in vessel number and/or a reduction in vessel lumen could reduce the number of vessels detected by MRA. In general, MRA cannot distinguish overt vessel loss and the loss of visualizable vessels as a result of decreased flow rate.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Underlying microvascular disease may contribute to many of these changes. [8][9][10][11] Larger vessels may also be affected; indeed, a recent MR angiography (MRA) study reported that even the larger vessels perceptible by MRA exhibit a loss of vessel number and a mild increase in vessel tortuosity during healthy aging. 12 The variability in the magnitude of age-related change is large, however, and the brains of some elderly subjects have the characteristics of the brains of much younger individuals.…”
mentioning
confidence: 99%